The Influence of additives on biodiesel blend for engine performance and emission improvement - Ali, Obed Majeed (2014)
Biodiesel is receiving more and more attention as a renewable fuel; serve as an alternative to mineral diesel. Fossil fuels are depleting with time due to their limited resources. On the other hand; the world energy consumption increases continuously due to the modern life requirements which lead to series energy crises. Although blended biodiesel-diesel fuel can replace mineral diesel satisfactorily at low blending ratios up to 20% biodiesel, problems related to fuel properties persist at high blending ratio more than 20%. The aim of this thesis is to investigate the feasibility of biodiesel-diesel blended fuel at 30% biodiesel, as fuel for unmodified diesel engines. Chemical additives are introduced as a viable option to improve the blended fuel properties. The experimental characterization of the blended fuel properties was conducted with ethanol, butanol and diethyl ether additives at low ratios up to 8% compared to the blended fuel standard ASTM D7467. Furthermore, engine is tested with blended fuel B30 and additives to investigate the engine performance, exhaust emissions and engine cyclic variations using the coefficient of variation and the wavelet analysis method. A statistically significant improvement in blended fuel kinematic viscosity and density was observed with all additives starting at 4% and 6% additive ratios for kinematic viscosity and density, respectively. On the other hand, a significant reduction in the blended fuel heating value was observed with all additive types starting at 6% additive ratio. The least reduction of blended fuel B30 heating value observed at 8% additive ratio is about 4% for B30 with diethyl ether additive. The blended fuel cold flow properties were improved with increasing additive ratios and maximum reduction in pour and cloud point was observed with diethyl ether by 2 oC and 3 oC respectively; at 8% additive ratio. The engine brake thermal efficiency was comparable for blended fuel B30 with different additives and mineral diesel. Furthermore, blended fuel with diethyl ether additive showed higher engine power at lower brake specific fuel consumption compared to other additives at similar ratios, and better engine brake power was achieved at 6% diethyl ether with increasing the additive ratio. The formation of NOx and CO2 emissions was reduced significantly with increasing the additive ratios. Better improvement in these emissions observed with diethyl ether additive at 8% ratio, which was comparable to that of diesel fuel. The significant impact of the additives on reducing the maximum in-cylinder pressure for B30 was observed with increasing additive ratios and the better trend obtained for B30 with 4% to 6% diethyl ether additive, which was comparable to that of the mineral diesel. Both the wavelet analysis and coefficient of variation reveal that increasing the additive ratio would give a noticeable effect on increasing the engine cycle-to-cycle variations which limits their usage at high ratios. It can be concluded that chemical additives are a viable option to introduce the blended fuel B30 as an alternative fuel for diesel engine that meets the blended fuel standard ASTM D7467 specifications.